Functional Constipation in Health Care Professionals at a University Hospital - Altay, Derya; Dogan, Yasar (Erciyes Univ Sch Medicine, 2018)
Objective: The objective of this study was to determine the frequency of functional constipation, which is a common functional gastrointestinal disorder, in health care professionals. Materials and Methods: In this study, a survey based on the Rome III criteria was conducted with personnel working at the Firat University to determine the frequency of functional constipation. The survey mainly focused on the nightshift personnel. For statistical analysis, p<0.05 was considered to be significant. Results: A total of 217 individuals participated and were evaluated in the survey. The mean age of the participants was 30.08+7.83 years, and 148 of them were females (68.2%). Seventy-three of these participants (33.2%) complained of constipation, and 47 (21.7%) stated that they were smokers. Fifty-seven of the participants (79.2%) who complained of constipation were females (p<0.05); 41 of them were married (56.9 %; p<0.05). One hundred and fifteen participants (53%) had nightshift on average 7.63+2.72 nights a month, and 42 of them (36.5%) complained of constipation (p>0.05). However, only one-fourth of participants with constipation used laxatives. A total of 23.6% of participants with constipation stated that their family members had similar issues (p<0.05). Conclusion: The results of this study showed that one-third of the health care personnel at the university hospital had constipation. We concluded that the productivity of the health care personnel, who play an important role in the examination and treatment process of the patients, will increase with training about functional constipation.
Keywords: Functional constipation; healthcare professionals; university hospital